Acute Megakaryoblastic Leukemia with Trisomy 21 and Tetrasomy 21 Clones in a Phenotypically Normal Child with Mosaic Trisomy 21 - Eric Won; Tanja A. Gruber; Suzanne Tucker; Deborah E. Schiff (Hindawi Limited, 2020)
Pediatric acute megakaryoblastic leukemia (AMKL) is a rare subtype of acute myeloid leukemia (AML) that may be divided into two subgroups: (1) Down syndrome- (DS-) related AMKL which generally has a favorable prognosis and (2) non-DS-related AMKL which generally has a poorer outcome. We report a phenotypically normal child with AMKL with trisomy 21 (T21) and tetrasomy 21 clones. Subsequently, she was diagnosed with mosaic T21. She underwent reduced-intensity therapy with good outcome. We review the literature regarding AMKL-associated cytogenetic abnormalities and AMKL in association with DS. We suggest evaluation for mosaic T21 in phenotypically normal pediatric patients with T21-positive AML.